Challenge of value: building customer value through understanding - Macdivitt, Harry (Henry Stewart Talks, 2010)
Role of value in all business transactions, Value concept poorly understood, Value Triad framework to analyse Value, Identifying and using Value Drivers, Importance of building Value thinking throughout the value chain